Comparison of Influence of Office and 24‐h Central Aortic Blood Pressure on Target Organ Damage in Hypertension - Yueliang Hu; Hui Yang; Guili Chang; Yaya Bai; Alberto Avolio; Qian Wang; Shenshen Gao; Junli Zuo (The Journal of Clinical Hypertension)
ABSTRACT The aim of this study was to explore whether 24‐h ambulatory central (aortic) blood pressure (BP) has an advantage over office central aortic BP in screening for hypertension‐mediated target organ damage (HMOD). A total of 714 inpatients with primary hypertension and the presence of several cardiovascular risk factors or complications involving clinical HMOD were enrolled. Twenty‐four hour central aortic BP was measured by means of a noninvasive automated oscillometric device (Mobil‐O‐Graph). Office BP was measured with a validated oscillometric Omron device after a 5‐min rest in a sitting position. Central aortic pressure waveforms were derived from the radial pressure waveforms with a validated transfer function of the Sphygmocor software, version 8.0 (Atcor Medical, Sydney, Australia). Carotid–femoral pulse wave velocity (cf‐PWV) measurement was performed by sequential placement of the transducer on the femoral artery and carotid artery and determining transit time between the two pulses in reference to the R wave of the ECG. cf‐PWV was calculated as the measured distance from the suprasternal notch to the femoral artery minus the distance from the suprasternal notch to the carotid artery divided by the pulse transit time. HMOD was defined as the presence of carotid intima–media thickness (IMT) above normal values and/or carotid plaque, left ventricular hypertrophy (LVH), renal abnormalities as assessed by urine albumin/creatinine ratio (ACR) above normal values and/or estimated glomerular filtration rate (eGFR) less than 60 mL/min/1.73 m2 and/or increased cf‐PWV > 10 m/s. In the study cohort of 714 (age 54.52 ± 13.24 years, 74.6% male) patients with primary hypertension, LV mass index (LVMI) was significantly higher in males (p < 0.002) and eGFR was significantly lower in males (p < 0.001). However, there was no statistical significance between males and females in IMT, ACR, and cfPWV. When accounting for confounding factors (age, sex, BMI, triglycerides, total cholesterol, LDL, glucose, smoking, and heart rate), central systolic (cSBP), diastolic (DBP), and pulse (cPP) pressure obtained with 24‐h monitoring was more strongly correlated with LVMI than office measurements. Twenty‐four hour cSBP and cPP were more strongly correlated with IMT than those of office monitoring. The 24‐h augmentation index (AIx) was more strongly correlated with eGFR than office AIX. Twnety‐four hour cSBP and cPP were more strongly correlated with lgACR. Office AIx and cPP were more strongly correlated with c‐fPWV than 24‐h measurements while cSBP, DBP, and cPP obtained by both methods were equally correlated with c‐fPWV. Ambulatory central (aortic) pressure may be more strongly related to HMOD than office CAP which may have an advantage in screening for c‐fPWV. Trial Registration: Registration number: ChiCTR2000040308